EXPERIMENTAL DETERMINATION OF THE SOLUBILITY OF REO2 AND THE DOMINANT OXIDATION STATE OF RHENIUM IN HYDROTHERMAL SOLUTIONS - Xiong Y.; Wood S.A. (My University, 1999)
The dominant oxidation state of rhenium in high-temperature, chloride-bearing hydrothermal solutions at geologically reasonable oxygen fugacities has been experimentally determined to be +4, although a small percentage of dissolved rhenium (=<10%) may be present in the +5 or higher valence state. This conclusion is based on a series of solubility experiments in 1.0 molal KCl solutions at 500°C using ReO2, the K-feldspar-muscovite-quartz assemblage as a pH buffer, and Co-CoO, Ni-NiO, Re-ReO2, MnO-Mn3O4, and MoO2-MoO3 pairs as oxygen fugacity buffers. Experiments were also conducted on the solubility of the Re-ReO2 oxygen fugacity buffer in 0.5 and 1.5 m KCl solutions in equilibrium with the K-feldspar-muscovite-quartz pH buffer at 500°C. The solubility of Re increases dramatically with increasing KCl concentration under these conditions, implying the formation of a Cl-bearing Re species. Because Re+4 is a hard acid owing to its high ionic potential, relatively hard ligands such as Cl-, F-, O2- and OH- should be important in the transport of Re during geological processes at elevated temperatures. Mixing/dilution, which may induce changes in pH and/or chloride concentration, should be important for the deposition of Re because the solubility of rhenium has a strong dependence on pH and the concentration of Cl-. Our experimental results may have implications for the hydrothermal remobilization and enrichment of rhenium in high-temperature environments, for the Re-Os isotopic system, and for the rhenium budget in the continental crust. Our study may also have bearing on the aqueous geochemistry of fissiogenic 99Tc, for which Re is an analogue. These implications are discussed in detail.
Keywords: RHENIUM DIOXIDE; TECHNETIUM; RE-OS ISOTOPIC SYSTEM; HYDROTHERMAL TRANSPORT; SOLUBILITY; RHENIUM BUDGET